(18)F-FDG Uptake in Lung, Breast, and Colon Cancers: Molecular Biology Correlates and Disease Characterization - Jadvar, Hossein (2009)
It is hoped that in the not too distant future, noninvasive imaging–based molecular interrogation and characterization of tumors can improve our fundamental understanding of the dynamic biologic behavior of cancer. For example, the new dimension of diagnostic information that is provided by (18)F-FDG PET has led to improved clinical decision making and management changes in a substantial number of patients with cancer. In this context, the aim of this review is to bring together and summarize the current data on the correlation between the underlying molecular biology and the clinical observations of tumor (18)F-FDG accumulation in 3 major human cancers: lung, breast, and colon.